2016
DOI: 10.4236/as.2016.78051
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Parametric Limitations in Simulating Greenhouse Gas Fluxes from Irish Arable Soils Using Three Process-Based Models

Abstract: Globally a large number of process-based models have been assessed for quantification of agricultural greenhouse gas (GHG) emissions. Modelling approaches minimize the presence of spatial variability of biogeochemical processes, leading to improved estimates of GHGs as well as identifying mitigation and policy options. The comparative performance of the three dynamic models (e.g., DNDC v9.4, DailyDayCent and ECOSSE v5+) with minimum numbers of common input parameters was evaluated against measured variables. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…Uncertainties in the observed values were also possible due to the limited number of field measurements (Parkin, 2008) as N2O is released in pulses from soils to the atmosphere (Hastings et al, 2010) and peaks may appear for a maximum of few weeks only (Bell et al, 2012). Khalil et al (2016) reported that it is important to use a robust measurement protocol to get accurate validation of the DNDC model in response to different management practices.…”
Section: Nitrous Oxide Emissionsmentioning
confidence: 99%
“…Uncertainties in the observed values were also possible due to the limited number of field measurements (Parkin, 2008) as N2O is released in pulses from soils to the atmosphere (Hastings et al, 2010) and peaks may appear for a maximum of few weeks only (Bell et al, 2012). Khalil et al (2016) reported that it is important to use a robust measurement protocol to get accurate validation of the DNDC model in response to different management practices.…”
Section: Nitrous Oxide Emissionsmentioning
confidence: 99%
“…Previous studies have evaluated the models DayCent, PaSim, and APSIM with N 2 O flux data from lab experiments and on grassland sites under different climatic and soil conditions (Abdalla et al, ; Ehrhardt et al, ; Giltrap et al, ; Khalil et al, ; Y. Li et al, ; W. J. Parton et al, ; Stehfest & Müller, ; Thorburn et al, ; Xing et al, ). While some studies focused on the performance of the average N 2 O flux estimates across sites (Ehrhardt et al, ), most evaluated the dynamics of N 2 O fluxes, usually using manual chamber measurements (Abdalla et al, ; Giltrap et al, ; Khalil et al, ; Stehfest & Müller, ; Zimmermann et al, ). For instance, Fitton et al () showed relative biases for DayCent for three UK sites ranging from −84% to +10%.…”
Section: Discussionmentioning
confidence: 99%
“…It has been extensively tested globally and has shown reasonable agreements between measured and modeled N2O emissions for many different ecosystems (e.g. Li, 2007;Kurbatova et al, 2009;Giltrap et al, 2010;Khalil et al, 2016;2018;…”
Section: Dndcmentioning
confidence: 99%